Adverse effect of anthropogenic activities on water quality of Kuantan River, Kuantan - Muhammad Ammarhariz, Hamdan (2017)
Nowadays, the condition of water in Malaysia are much polluted and becoming more serious because the water quality is in bad condition due to anthropogenic activity that was carried out. For this study, the Kuantan River has been chosen for water quality which were located at 03°50.9° latitude and 103°29.2° within the capital state of Pahang with length 440km respectively. The Kuantan River was chosen as the sampling site because it is believed that this river has been polluted with several kinds of pollution. The objectives of this study were to determine the characteristic of water quality based on National Quality Standard (NWQS) and Water Quality Index (WQI) and to identify the causes and sources of pollutant for sustainable management of the Kuantan industrial area. To achieve this objective, three times of water samples were collected from March to May 2017 at the three different stations along the Kuantan River. All of the stations were about 5 to 6 meters from drains that discharged water from the expected polluted area. Physical and chemical parameters were analyse using standard methods. The WQI was calculated based on the concentration of pH, total suspended solid (TSS), ammonia nitrogen (NH3-N), chemical oxygen demand (COD), biochemical oxygen demand (BOD) and dissolved oxygen (DO). Other parameters that were analyse in this study were turbidity, temperature, electrical conductivity (EC) and selected heavy metal which are cadmium (Cd) and copper (Cu). Result from this study showed that the values of WQI at each station were in the range 80.53-83.08 that in the Class II-III. The WQI score value at Station 1, 2 and 3 were 82.30, 83.08, and 80.53 respectively. The status of this river was in clean and slightly polluted condition. In NWQS, the Kuantan River is classified under Class I-III. The highest concentration of copper is at station 3 during sampling 1. The lowest concentration of cadmium is at station 2 during sampling 2. The main factors of anthropogenic activities that influence the degradation of water quality were sewerage and drainage in a residential area, construction activities, agricultural and forested that near the river. The suggestion for sustainable management to overcome water pollution problem is regularly inspect and maintenance to ensure the septic tank and sewage is properly operate.